1997
DOI: 10.1038/bjc.1997.21
|View full text |Cite
|
Sign up to set email alerts
|

Continued inadequacies in data sources for the evaluation of cancer services

Abstract: Summary There is a need to evaluate cancer services and provide a baseline on current treatment success and organization. This study shows that this process may be severely hindered by case note destruction or inaccessibility and incomplete information. This is an ongoing problem that needs to be addressed now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Cancer registries are the primary source of surveillance data for cancer incidence, yet several studies have shown that the completeness and accuracy of cancer registries data varies (Rushton & Romaniuk, 1997; Smith et al , 1997; Cartwright, 1999; Bullard et al, 2000). Our study emphasizes the imperfections in both registers of completeness, case ascertainment, timeliness and diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer registries are the primary source of surveillance data for cancer incidence, yet several studies have shown that the completeness and accuracy of cancer registries data varies (Rushton & Romaniuk, 1997; Smith et al , 1997; Cartwright, 1999; Bullard et al, 2000). Our study emphasizes the imperfections in both registers of completeness, case ascertainment, timeliness and diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Et slikt system med tett kontakt mellom sykehus og Kreftregisteret har ikke bare rasjonalisering som hensikt, men kvalitetssikring. Erfarin-ger fra Norge og andre land viser at det er meget vanskelig å få komplette data av høy kvalitet både om primaerdiagnosen og om tilbakefall uten meget sterk lokal medvirkning (18). Den ekstra ressursinnsatsen som her skytes inn, vil gi en stor kvalitetsforbedring av registerdatabasen, som igjen vil gi grunnlaget for meningsfylt kvalitetssikring og -kontroll av kreftbehandlingen.…”
Section: B) Samkjøring Med Andre Registre For å Oppnå Kompletthet Og unclassified